Mixed convection of MHD Reiner–Philippoff fluid flow past a vertical shrinking plate with radiative heat transfer - Iskandar, Waini; Nurul Amira, Zainal; Najiyah Safwa, Khashi’ie; Khairum, Hamzah; Abdul Rahman, Mohd Kasim; Anuar, Mohd Ishak; Pop, Ioan Mihai (Elsevier B.V., 2023)
The mixed convection and radiative flow with thermal characteristics of a non-Newtonian Reiner–Philippoff fluid towards a permeable vertical plate are analysed in this study. This unique model is designed to observe both shear thickening and shear thinning behaviours in that particular fluid. The governing equations are constructed using the theoretical assumptions and then reduced to a set of ordinary differential equations (ODEs). The steady flow solutions are computed using the Matlab software bvp4c. Dual solutions are observed and their physical significance is justified using the temporal stability analysis. The thermal development of this fluid is aided by the employment of the magnetic field and suction effect. However, the high magnitude of the radiation parameter leads to the deterioration in the thermal rate. From the standpoint of the Reiner–Philippoff fluid parameter, the skin friction coefficient and heat transfer rate are at maximum for the shear-thickening fluid followed by the Newtonian and shear-thinning fluids, respectively.